Evidence for more than one division of bacteria within airborne particles. - Dimmick, R L (1979)
When the protocol that we had used to demonstrate a single division of bacterial cells in airborne particles was changed to one that increased the glycerol content of the atomizer fluid from 1 to 5% (vol/vol), thus producing larger particles, more than two (and nearly three) divisions of bacteria occurred within 6 h of aerosol time.